Interview to Esteban Hernández Esteve conducted by prof. Oktay Güvemli, convenor of the 12th WCAH - Güvemli, Oktay (De Computis, Revista Española de Historia de la Contabilidad., 2008)
Interview to Esteban Hernández Esteve conducted by prof. Oktay Güvemli, convenor of the 12th WCAH